2015
DOI: 10.3923/ajcb.2015.43.56
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Expression Level of Macrophage Cell, Pro-Inflammatory Cytokines and NF-κB by Using VipAlbumin® in vitro

Abstract: Inflammation is a physiological response to an injury and disruption by the external factor. VipAlbumin ® is a one of the supplement that has anti-inflammatory activity. This study wants to know the effect of VipAlbumin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Pro-inflammatory cytokine TNF-α, IFN-γ and IL-6 are included among the group pro-inflammatory cytokines that can cause chronic inflammation (Dwijayanti et al, 2015). As shown in Figure 1, this study showed that the relative amount of TNF-α and IFN-γ secreted by CD4 + T cells, and IL-6 and IFN-γ secreted by macrophages (CD11b + ), was significantly increased (p < .05) in inflammatory conditions when compared to the control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro-inflammatory cytokine TNF-α, IFN-γ and IL-6 are included among the group pro-inflammatory cytokines that can cause chronic inflammation (Dwijayanti et al, 2015). As shown in Figure 1, this study showed that the relative amount of TNF-α and IFN-γ secreted by CD4 + T cells, and IL-6 and IFN-γ secreted by macrophages (CD11b + ), was significantly increased (p < .05) in inflammatory conditions when compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…These chemical factors are released by inflammation-mediating cells that act in the immune system to protect tissue from infection. Prolonged inflammation (called chronic inflammation) can lead to various diseases such as autoimmune diseases, diabetes mellitus, cardiovascular diseases, pulmonary diseases and cancer (Dwijayanti, Djati, & Rifa'i, 2015;Yen et al, 2006). Therefore, chronic inflammation must be treated immediately to prevent these dangerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It can also increase IGF-1 levels and decrease IL-6 levels, which are important factors in sarcopenia. Several studies have shown decreases in IL-6 and TNF-α levels after using Ophiocephalus striatus extract [ 12 , 18 , 22 ]. A study on cancer patients with cachexia found a significant reduction in IL-6 levels after two weeks of using Ophiocephalus striatus extract [ 18 ].…”
Section: Introductionmentioning
confidence: 99%